2020
DOI: 10.1097/jxx.0000000000000311
|View full text |Cite
|
Sign up to set email alerts
|

Nurse practitioner interventions for smokers with chronic hepatitis C

Abstract: Background: Smoking is a grossly overlooked risk factor for people with chronic hepatitis C with regard to disease progression. It is unclear whether current smoking cessation interventions are effective for this population. Purpose: The purpose was to evaluate the effectiveness of a telephone counseling and nicotine replacement therapy (NRT) intervention for smokers with chronic hepatitis C to quit or reduce rates of smoking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…All of the studies were published between 2010 and 2019. Four studies were conducted in Hong Kong (Chan et al, 2012; Li et al, 2017, 2018; Leung et al, 2019), two in the United States (Ellerbeck et al, 2018; Hennrikus et al, 2010), two in China (Lou et al, 2013; Zhou et al, 2017), one in Australia (Reid et al, 2020) and one in India (Thankappan et al, 2013). In terms of design, nine studies were RCTs (Chan et al, 2012; Li et al, 2017, 2018; Ellerbeck et al, 2018; Hennrikus et al, 2010; Leung et al, 2019; Lou et al, 2013; Reid et al, 2020; Thankappan et al, 2013), and one was a non‐RCT (Zhou et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All of the studies were published between 2010 and 2019. Four studies were conducted in Hong Kong (Chan et al, 2012; Li et al, 2017, 2018; Leung et al, 2019), two in the United States (Ellerbeck et al, 2018; Hennrikus et al, 2010), two in China (Lou et al, 2013; Zhou et al, 2017), one in Australia (Reid et al, 2020) and one in India (Thankappan et al, 2013). In terms of design, nine studies were RCTs (Chan et al, 2012; Li et al, 2017, 2018; Ellerbeck et al, 2018; Hennrikus et al, 2010; Leung et al, 2019; Lou et al, 2013; Reid et al, 2020; Thankappan et al, 2013), and one was a non‐RCT (Zhou et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported the years of smoking (Chan et al, 2012; Li et al, 2017, 2018; Hennrikus et al, 2010; Leung et al, 2019; Thankappan et al, 2013; Zhou et al, 2017). One study only reported the change in the Fagerström Test for Nicotine Dependence score but did not provide a baseline score (Reid et al, 2020). Taken together, these studies showed that most participants had a long history of heavy smoking and a high level of nicotine dependency.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations